The R chondrite record of volatile-rich environments in the early solar system - Miller, Kelly Elizabeth (The University of Arizona, 2016)
Chondritic meteorites are undifferentiated fragments of asteroids that contain the oldest solids formed in our Solar System. Their primitive, solar-like chemical compositions indicate that they experienced very little processing following accretion to their parent bodies. As such, they retain the best records of chemical and physical processes active in the protoplanetary disk during planet formation. Chondritic meteorites are depleted relative to the sun in volatile elements such as S and O. In addition to being important components of organic material, these elements exert a strong influence on the behavior of other more refractory species and the composition of planets. Understanding their distribution is therefore of key interest to the scientific community. While the bulk abundance of volatile elements in solid phases present in meteorites is below solar values, some meteorites record volatile-rich gas phases. The Rumuruti (R) chondrites record environments rich in both S and O, making them ideal probes for volatile enhancement in the early Solar System. Disentangling the effects of parent-body processing on pre-accretionary signatures requires unequilibrated meteorite samples. These samples are rare in the R chondrites. Here, I report analyses of unequilibrated clasts in two thin sections from the same meteorite, PRE 95404 (R3.2 to R4). Data include high resolution element maps, EMP chemical analyses from silicate, sulfide, phosphate, and spinel phases, SIMS oxygen isotope ratios of chondrules, and electron diffraction patterns from Cu-bearing phases. Oxygen isotope ratios and chondrule fO2 levels are consistent with type II chondrules in LL chondrites. Chondrule-sized, rounded sulfide nodules are ubiquitous in both thin sections. There are multiple instances of sulfide-silicate relationships that are petrologically similar to compound chondrules, suggesting that sulfide nodules and silicate chondrules formed as coexisting melts. This hypothesis is supported by the presence of phosphate inclusions and Cu-rich lamellae in both sulfide nodules and sulfide assemblages within silicate chondrules. Thermodynamic analyses indicate that sulfide melts reached temperatures up to 1138 °C and fS 2 of 2 x 10-3 atm. These conditions require total pressures on the order of 1 atm, and a dust- or ice-rich environment. Comparison with current models suggest that either the environmental parameters used to model chondrule formation prior to planetesimal formation should be adjusted to meet this pressure constraint, or R chondrite chondrules may have formed through planetesimal bow shocks or impacts. The pre-accretionary environment recorded by unequilibrated R chondrites was therefore highly sulfidizing, and had fO 2 higher than solar composition, but lower than the equilibrated R chondrites. Chalcopyrite is rare in meteorites, but forms terrestrially in hydrothermal sulfide deposits. It was previously reported in the R chondrites. I studied thin sections from PRE 95411 (R3 or R4), PCA 91002 (R3.8 to R5), and NWA 7514 (R6) using Cu X-ray maps and EMP chemical analyses of sulfide phases. I found chalcopyrite in all three samples. TEM electron diffraction data from a representative assemblage in PRE 95411 are consistent with this mineral identification. TEM images and X-ray maps reveal the presence of an oxide vein. A cubanite-like phase was identified in PCA 91002. Electron diffraction patterns are consistent with isocubanite. Cu-rich lamellae in the unequilibrated clasts of PRE 95404 are the presumed precursor materials for chalcopyrite and isocubanite. Diffraction patterns from these precursor phases index to bornite. I hypothesize that bornite formed during melt crystallization prior to accretion. Hydrothermal alteration on the parent body by an Fe-rich aqueous phase between 200 and 300 °C resulted in the formation of isocubanite and chalcopyrite. In most instances, isocubanite may have transformed to chalcopyrite and pyrrhotite at temperatures below 210 °C. This environment was both oxidizing and sulfidizing, suggesting that the R chondrites record an extended history of volatile-rich interaction. These results indicate that hydrothermal alteration of sulfides on the R chondrite parent body was pervasive and occurred even in low petrologic types. This high temperature aqueous activity is distinct from both the low temperature aqueous alteration of the carbonaceous chondrites and the high temperature, anhydrous alteration of the ordinary chondrites.